The Effect of Return on Equity, Debt to Equity Ratio, and Book Value Per Share on Stock Prices (Case Study of Plastic and Packaging Companies Listed on The Bei For The Period 2019-2022) - Nur Fatdhiloh, Inayah Asliqhah; Dyah Kusumastuti, Anggit; Paningrum, Destina (Muhasabatuna : Jurnal Akuntansi Syariah, 2024)
This study aims to test and analyze the effect of Return On Equity (ROE), Debt to Equity Ratio (DER), and Book Value Per Share (BVS) on the share price of plastic and packaging companies listed on the IDX for the 2019-2022 period. The population and samples in this study are plastic and packaging companies listed on the Indonesia Stock Exchange (IDX). Sampling in this study uses purposive sampling technique, the type of research used is explanatory research with a quantitative approach. The data source in this study is secondary data obtained from the company's financial statements. The analysis method used is multiple linear regression analysis. The results of this study indicate that Return On Equity (ROE) and Debt to Equity Ratio (DER) have a positive and significant effect on stock prices, while Book Value Per Share (BVS) has no effect on stock prices.